2016
DOI: 10.21746/ijbio.2016.06.0011
|View full text |Cite
|
Sign up to set email alerts
|

Hepato-renal protective effects of gallic acid and p-coumaric acid in nicotinamide/streptozotocin-induced diabetic rats

Abstract: The goal of diabetes treatment is primarily to save life and alleviate symptoms and secondary to prevent long-term diabetic complications resulting from hyperglycemia. Thus, our present investigation was designed to evaluate the hepato-renal protective effects of gallic acid and p-coumaric acid in nicotinamide/streptozotocin (NA/STZ)-induced diabetic rats. Experimental type 2 diabetes was induced by a single intraperitoneal (i.p.) injection of STZ (65 mg/kg b.wt.), after 15 min of i.p. injection of NA (120 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
(49 reference statements)
3
2
0
Order By: Relevance
“…In agreement with Gupta et al (2011) and Moneim et al, (2016) the untreated diabetic models showed a highly significant increase in protein level in urine compared with the control group. High proteinuria may be as a result of increased advanced oxidative protein products, reactive oxygen species and free radicals producing protein carbonyl products and due to increasing the permeability of the glomerular membrane (Madianov et al 2000).…”
Section: The Mean Alpha Sma Stained Area Percentagesupporting
confidence: 91%
“…In agreement with Gupta et al (2011) and Moneim et al, (2016) the untreated diabetic models showed a highly significant increase in protein level in urine compared with the control group. High proteinuria may be as a result of increased advanced oxidative protein products, reactive oxygen species and free radicals producing protein carbonyl products and due to increasing the permeability of the glomerular membrane (Madianov et al 2000).…”
Section: The Mean Alpha Sma Stained Area Percentagesupporting
confidence: 91%
“…Consequently, the activities of liver damage markers of ALT and AST enzymes increased in the untreated diabetic patients [132,133]. These data run in parallel with the results of Ahmed et al [95] and Moneim et al [134]. The C. reticulata peel hydroethanolic extract, hesperidin, and quercetin have a defensive effect against the hepatotoxicity produced by STZ-induced DM; their effects are nearly similar.…”
supporting
confidence: 84%
“…In the present study, ALT and AST activities in the toluene+p-CA group were significantly (p<0.05) higher than in the toluene group. Similar to the present study, p-CA in serum samples decreased ALT and AST activities, and cretainine level (41,42,43,44).…”
Section: Discussionsupporting
confidence: 89%